2018
DOI: 10.3389/fnins.2018.00602
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-298 Reverses Multidrug Resistance to Antiepileptic Drugs by Suppressing MDR1/P-gp Expression in vitro

Abstract: P-glycoprotein (P-gp), a critical multidrug transporter, recognizes and transports various antiepileptic drugs (AEDs) through the blood-brain barrier (BBB). This may decrease the concentrations of AEDs in brain tissues and cause multidrug resistance (MDR) in patients with refractory epilepsy. Compelling evidence indicates that microRNAs (miRNAs) modulate MDR in various cancers by regulating P-gp expression. Furthermore, a previous study showed that miR-298 mediates MDR in breast cancer cells by downregulating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 33 publications
1
25
0
Order By: Relevance
“…The establishment of the PHT-resistant cell line was described in our previous study (Xie et al, 2018). In the present study, it was observed that the expression of P-gp was significantly elevated in HBMEC/PHT cells as determined by IF staining (Figure 1A).…”
Section: The Expression Of Kcnq1ot1 Is Upregulated In Pht-resistant Hsupporting
confidence: 77%
“…The establishment of the PHT-resistant cell line was described in our previous study (Xie et al, 2018). In the present study, it was observed that the expression of P-gp was significantly elevated in HBMEC/PHT cells as determined by IF staining (Figure 1A).…”
Section: The Expression Of Kcnq1ot1 Is Upregulated In Pht-resistant Hsupporting
confidence: 77%
“…Specific mechanisms of drug resistance mediated by miRNAs are under ongoing investigation. Accumulating evidence, however, shows that the ATP-binding cassette (ABC) transporter family of proteins that activate drug resistance are regulated by miRNAs (Guo et al., 2018; Xie et al., 2018). The ABC family includes P-glycoprotein (Pgp), multidrug resistance-associated proteins (MRP), and breast cancer resistance proteins (BCRP), all of which can pump out drugs to create additional biological energy through ATP hydrolysis (Choi, 2005; Paskeviciute and Petrikaite, 2019).…”
Section: Drug Resistance and Mirnasmentioning
confidence: 99%
“…Other mRNAs, including miR-298, mediate the downregulation of Pgp [ 50 ]. Recently, it was shown that miR-298 reverses multidrug resistance to ASDs by downregulating Pgp expression in the BBB, using human BCECs [ 51 ].…”
Section: Regulation Of Pgp At the Bbb: Conventional Mechanismsmentioning
confidence: 99%